(untitled) (American Journal of Islam and Society, 2024)
The discourse on the relationship between Islam and democracy has been thrust into the limelight amidst the backdrop of the “War on Terror.” From this ongoing dialogue, three overarching perspectives have emerged, each shedding a unique light on this complex nexus: Firstly, there is the belief that Muslim societies inherently lack the capacity to cultivate a liberal culture, thereby hindering the attainment of democracy in Muslim-majority nations. This viewpoint is often propelled by Western media narratives. Contrastingly, a second perspective asserts that democracy not only aligns with Islamic principles but contends that historical Islamic polities have exemplified democratic values more profoundly than any other system worldwide. Lastly, a third viewpoint dismisses democracy as a foreign concept, incompatible with the Islamic tradition, and inherently Western in nature. These last two perspectives find resonance within Muslim intellectual circles.